A Study to Assess the Effectiveness of Mindful Meditation on Health and Psychological Adjustment Faced by Nursing Students in Selected Colleges of Pune City - Anu Alexander1 , Ms. Feba Josemon1 , Shreeti Gahare1 , Neha Jadhav1 , Sonopant G Joshi2 , Ranjana Ch (Indian Journal of Forensic Medicine & Toxicology, 2020)
Nursing students experiences more stress in their early academic period. Psychological adjustment becomesdifficult for them due to many challenges. It is assumed that mindful meditation will helpful for them tocope up with adjustment problems. A study to assess the effectiveness of mindful meditation on healthand psychological adjustment faced by first year B.Sc nursing students in selected nursing college of Punecity. Purpose of the study to assess the level of health and psychological adjustment and evaluation ofmindful meditation on their adjustment. Pre-experimental study was conducted to find out the adjustmentproblems. The research design was one group pre-test post-test experimental design. The sample size was40. Purposive sampling technique was used to select the students. The result showed that first year B ScNursing students faces multiple adjustment problems related to their health and psychological adjustments.Mindful Meditation in early academic life was proved very useful in adjusting the new world of academicenvironment.